Investigação da noção de classificação em crianças de dez anos utilizando o Método Psicométrico e o Método Clínico - Ogioni, Fernanda Schiavon (2011)
The main purpose of this dissertation is to study the classification notion of tenyear-old children through in two investigation approaches: the Clinical method and the Psychometric method. The class inclusion test and the Logic Blocks were used as instruments for the clinical investigation, while the subtest Similarities was set as an instrument under the Psychometric reference. The responses obtained through the Clinical method were analyzed under the levels proposed by Piaget and Inhelder (1983), which refer to the classification notion, while the responses obtained through the subtest were corrected and scored according to the material correction criteria, which classifies the answers as incorrect, concrete or abstract. The presented results clarify the distinctions between the studied methods: the Psychometric method allowed the classification investigation of the answers given by the participants, following a score and a description set by the empiric studies which provided the basis for the test development. On the other hand, the Clinical method allowed an approach focused on the process used by the children to build their answers. It may be understood that the methods' different purposes lead to different results, each one intending to achieve the goals they were created for.